The Effectiveness of the Implementation of Law Number 16 of 2019 Concerning Amendments to Law Number 1 of 1974 Concerning Marriage in Reducing the Number of Early Child Marriages in Balusu District, Barru Regency - Sri Hardianti Lukman; Rahmi Rais (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal